2019
DOI: 10.1177/2309499019857250
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic obliquity in adolescent idiopathic scoliosis planned for posterior spinal fusion: A preoperative analysis of 311 lower limb axis films

Abstract: To analyze the incidence, pattern, and contributing factors of pelvic obliquity among Adolescent Idiopathic Scoliosis (AIS) patients who will undergo surgery. Methods: In total, 311 patients underwent erect whole spine anteroposterior, lateral and lower limb axis films. Radiographic measurements included Transilium Pelvic Height Difference (TPHD; mm), Hip Abduction-Adduction angle (H/Abd-Add;), Lower limb Length Discrepancy (LLD; mm), and Pelvic Hypoplasia (PH angle;). The incidence and severity of pelvic obli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
(26 reference statements)
2
20
0
Order By: Relevance
“…In the current study, pelvic obliquity was positively correlated with LLD. Our findings were consistent with the conclusion reached by Young et al 39 Chan et al found that 24.6% of patients with pelvic obliquity ≥10 mm had such cases attributed to LLD 40 . A previous report demonstrated that THA patients with leg length inequalities need to be compensated differently from those patients without THA 30 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, pelvic obliquity was positively correlated with LLD. Our findings were consistent with the conclusion reached by Young et al 39 Chan et al found that 24.6% of patients with pelvic obliquity ≥10 mm had such cases attributed to LLD 40 . A previous report demonstrated that THA patients with leg length inequalities need to be compensated differently from those patients without THA 30 .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistent with the conclusion reached by Young et al 39 Chan et al found that 24.6% of patients with pelvic obliquity ≥10 mm had such cases attributed to LLD. 40 A previous report demonstrated that THA patients with leg length inequalities need to be compensated differently from those patients without THA. 30 As shortening of the affected leg might be accommodated by pelvic obliquity and the development of spine scoliosis, it is common to observe compensation of the pelvis‐spine complex.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative changes in pelvic obliquity were reported by Chen et al [13] . They described how pelvic obliquity could improve following the correction of scoliosis, but did not improve in the presence of structural problems such as pelvic hypoplasia.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, LLD did not improve after surgery in almost all patients with shortened right leg and in half of patients with shortened left leg. These results suggest that various factors other than scoliosis are involved in the development of functional LLD, including pelvic/trunk rotation and pelvic asymmetry [13] .…”
Section: Discussionmentioning
confidence: 80%
“…We used the crossbar method reported in the literature [ 18 ] and improved this method in practice. To avoid the influence of leg length discrepancies and pelvic inclination [ 19 , 20 ], the patients were required to try to straighten both lower extremities during preoperative radiography of the entire spine, and the S1 tilt was measured precisely, which should be consistent with the angle between the crossbar and the sacrum intraoperatively. On this basis, the angle between the upper endplate of the UIV and the crossbar should be consistent with the ideal postoperative UIV tilt calculated preoperatively.…”
Section: Methodsmentioning
confidence: 99%